Pengelolaan Organisme Pengganggu Tanaman Buncis Di Kelurahan Buraen, Kecamatan Amarasi Selatan, Kabupaten Kupang - Nahas, Agustina Etin; Mudita, I Wayan; Mau, Yosep Seran; Kadja, Don H.; Asbanu, Junior M.P.; Efantry, Febrianus (Jurnal Pengabdian Kepada Masyarakat Undana, 2023)
AbstractThis Community Partnership Program activity aims to increase farmers' knowledge and skills regarding techniques for controlling plant pest organisms (OPT) for beans, in addition to the use of insecticides. The Ruanrete Farmers Group is located in Buraen Village, South Amarasi District, Kupang Regency. Farmers have been carrying out bean cultivation activities using makeshift agricultural equipment manually without new, more modern technology. This area has springs, but farmers have not utilized them optimally. Based on these conditions, through this PKM, outreach activities were carried out regarding the cultivation of chickpeas and the management of pest organisms, training and experimental demonstration plots for managing chickpea pests with yellow traps from used mineral water bottles and environmentally friendly black and silver plastic mulch, guidance and assistance as well as evaluations for find out the obstacles experienced by partner farmers regarding the success of PKM activities. At the end of the activity, farmer group members gained knowledge and skills regarding pests that damage bean plants, how to install black and silver plastic mulch, how to make yellow traps and install them in the field to control pests using environmentally friendly waste mineral water bottles. Overall, farmers were very enthusiastic about receiving the technology introduction which was delivered from preparation, implementation to demonstration plot activities well and smoothly.